A flexible approach to combating chromatic dispersion in a centralized 5G network - Ilgaz, M. A.; Baliž, K. Vuk; Batagelj, B. (Opto-Electronics Review, 2020)
This article proposes and examines a solution in which the base-station for the fifth generation radio access network is simplified by using a single millimeter-wave oscillator in the central-station and distributing its millimeter-wave signal to the base-stations. The system is designed in such a way that the low-phase-noise signal generated by an opto-electronic oscillator is transmitted from the central-station to multiple base-stations via a passive optical network infrastructure. A novel flexible approach with a single-loop opto-electronic oscillator at the transmitting end and a tunable dispersion-compensation module at the receiving end(s) is proposed to distribute a power-penalty-free millimeter-wave signal in the radio access network. Power-penalty-free signal transmission from 10 MHz up to 45 GHz with an optical length of 20 km is achieved by a combination of a tunable dispersion-compensation module and an optical delay line. In addition, measurements with a fixed modulation frequency of 39 GHz and discretely incrementing optical fiber lengths from 0.625 km to 20 km are shown. Finally, a preliminary idea for an automatically controlled feedback-loop tuning system is proposed as a further research entry point.